The impact of changes in oil price on stock market: Evidence from Africa - Ikechukwu Kelikume; Omotayo Muritala (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
This study examined the impact of oil price on African stock markets. Using quarterly data from five selected oil producing countries with stock market presence, from Q1:2010 to Q4:2018, the study deployed dynamic panel analysis technique for a model comprising stock returns, real gross domestic product growth rate, exchange rate and OPEC basket price. From the findings, an adverse effect of oil prices existed on stock markets in Africa, attributable to fragmented and underdeveloped capital markets. Also, real gross domestic product growth rate had a positive impact on African stock markets, thus, confirming that economic growth positively influences stock returns in the African stock markets. The relationship exhibited by stock markets and the oil price has an immediate implication of shifting foreign direct investments in and away from stock markets in African oil-dependent economies. Based on the empirical findings, the study recommended that oil-exporting developing countries should devise strategies that can ensure stability in their capital markets by vigorously pursuing pro-growth policies irrespective of the shocks in oil price and other exogenous macroeconomic indicators.
Keywords: C32; C87; G12; N27; Q41; 330; Stock returns; oil price; exchange rate; African countries; unit root; panel regression